FORMULASI DAN EVALUASI SEDIAAN SPRAY GEL EKSTRAK BUNGA MARIGOLD (Tagetes Erecta L) SEBAGAI ANTIOKSIDAN - Imas Maesaroh; Lilik Fahmilik (Jurnal Komunitas Farmasi Nasional, 2021)
Marigold flower ( Tagetes erecta L) has the main component in petals namely lutein. Lutein is a natural color substance of the carotenoid group that is a powerful antioxidant and can contribute to covering cells against damage caused by free radicals. in this study researchers wanted to formulate marigold flower extract into spray gel ready. The manufacture of preparations is carried out using the method of maceration, after the stage of making preparations is carried out a ready evaluation that includes organoleptis test, homogeneity, viscosity, scattering, spraying pattern and chemistry (pH). Spray Gel is made in 3 Formulas namely F1, F2, and F3 which have differences in carbopol concentration. for F1 are carbopol 0.4%; F2 0.6% and F3 0.8%. Spray Gel resulting marigold flower extract is clear yellow color, diluted gel and oleum rosae smell. in addition, these three available also have a qualified pH of 5, in the homogeneity test these three gels produced homogeneous available, for F1 viscosity 360,911cps, F2 3,234cps, F3 3,868cps, for Formula 1 0 dispersal power test and formula 2 showed even dispersal power, while formula 3 showed the supply did not spread but only accumulated at one spray point only , Spraying Pattern Test that is Formula 1 and 2 tends to produce an elongated and diffuse spray pattern whereas in formula 3 it is only at one point straight from the spray.